A CONTRIBUTION TO THE STUDY OF THE GENUS DIPLYCOSIA (ERICACEAE) IN SULAWESI, INDONESIA. (24th February 2014) - Argent, G.
<x content-type="archive" xml:space="preserve">Abstract</x> New taxa and records of Diplycosia (Ericaceae) from recent expeditions to Sulawesi are described. Diplycosia balgooyi Argent, D. gallowayana Argent, D. glaucicaulis Argent, D. hendriana Argent and D. supyanii Argent are described as new species. Diplycosia minutiflora Sleumer var. glandulifera Argent is described as a new variety and the new combination D. capitata Sleumer var. crassiramea (Sleumer) Argent is made. A key to all the known species of Diplycosia from this island is provided, together with short descriptions of the previously described species.